PENERAPAN SISTEM INFORMASI AKUNTANSI PENERIMAAN PENDAPATAN PADA PT KERETA API INDONESIA SURABAYA - Putri, Nena BertaVirde (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This main to evaluate the implementation of accounting information system of receipt of income at PT Kereta Api Indonesia Surabaya. This research is a qualitative research, while the data analysis technique which isapplied in this research is the descriptive analysis with qualitative approach. The results of data interpretation and analysis to the implementation of accounting information system at PT Kereta Api Indonesia Surabaya, itcan be concluded that the organization structure of PT Kereta Api Indonesia Surabaya overall is good, incarrying out the activity of receipt of income has been using serial numbered document in order to prevent theoccurrence of deviation, so it can be said that the input of accounting information system of income is good.Output of accounting information system of income at PT Kereta Api Indonesia Surabaya can be said good,since the output consists of: daily sales reports, deposit books, cash book as well as the combined list and analysisof passengers revenue and the implementation of internal control of receipt of income at PT Kereta Api IndonesiaSurabaya it can be said good.Keywords: Accounting Information System, Income,Internal Control.